Role of B site ions in bifunctional oxygen electrocatalysis: a structure–property correlation study on doped Ca2Fe2O5 brownmillerites. Issue 27 (1st July 2020) - Thundiyil, Shibin; Vinod, C. P.; Kurungot, Sreekumar; Devi, R. Nandini
Abstract : Evaluation of activity descriptors for electrochemical bifunctional oxygen catalysis in transition metal doped Ca2 Fe2 O5 brownmillerite oxide. Abstract : The role of B site doping with transition metals in brownmillerites, a perovskite related family of compounds, in bifunctional oxygen electrocatalysis, viz., simultaneous reduction and evolution reactions, is analysed. Ca2 Fe1.9 M0.1 O5 (M = Mn, Co, Ni, and Cu) is synthesised and structurally characterised by powder XRD and Rietveld refinement. Valence states of the surface B site ions are identified by X-ray photoelectron spectroscopy. Bifunctional oxygen electrochemistry is studied with the RDE and RRDE techniques and correlated with the structural and electronic parameters like oxygen non-stoichiometry and B site catalytic activity. Since the widely accepted electronic descriptors like eg filling may not be sufficient for explaining the bifunctional activity, B site electron donating capability as well as the extent of oxygen vacancies enhancing O2 adsorption is also considered. Such structural parameters are also found to influence both the ORR and OER and based on this, Ni doping is proposed as advantageous for the bifunctional activity.